Zika puzzle in Brazil: peculiar conditions of viral introduction and dissemination - A Review - Cristina Possas; Patricia Brasil; Mauro CA Marzochi; Amilcar Tanuri; Reinaldo M Martins; Ernesto TA Marques; Myrna C Bonaldo; Antonio GP Ferreira; Ricardo Lourenço-de-Oliveira; Rita Maria R Nogueira; Patricia C Sequeira; Keyla BF Marzochi; et al. (Memorias do Instituto Oswaldo Cruz)
This article discusses the peculiar conditions that favoured the unexpected introduction of Zika virus into the poorest northeastern region of Brazil in 2015, its speed of transmission to other Brazilian states, other Latin American countries and other regions, and the severity of related neurological disorders in newborns and adults. Contrasting with evidence that Zika had so far caused only mild cases in humans in the last six decades, the epidemiological scenario of this outbreak in Brazil indicates dramatic health effects: in 2015, an increase of 20-fold in notified cases of microcephaly and/or central nervous system (CNS) alterations suggestive of Zika congenital infection, followed by an exponential increase in 2016, with 2366 cumulative cases confirmed in the country by the end of December 2016. A significant increase in Guillain-Barré syndrome in adults has also been reported. Factors involved in viral dissemination, neural pathogenesis and routes of transmission in Brazil are examined, such as the role of social and environmental factors and the controversies involved in the hypothesis of antibody-dependent enhancement, to explain the incidence of congenital Zika syndrome in Brazil. Responses to the Zika outbreak and the development of new products are also discussed.